Refleksi Nalar Budaya Pendidikan Islam dan dampaknya dalam Perilaku Sosial Keagamaan - Ali Riyadi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
Islamic education approaches religion as a social framework by carrying out critical reflections on social problems faced by society, both macro and micro, then building a change strategy (theory) that is practised in the form of action change (practice). In praxis, education builds a character's culture of educational behaviour as values ​​and behavioural characters. This study discusses the important role of Islamic educational institutions as agents of the development of science that have an impact on cultural social religious behavior. The results of this study indicate education in the formation of culture is an indoctrination as a process that is carried out based on a value system to instil certain ideas, attitudes, systems of thought, behaviour and beliefs. This practice is often distinguished from education because, in this act, an indoctrinated person is expected not to question or critically test the doctrine that has been learned.